Brasil no limiar do direito internacional dos refugiados: o Itamaraty e a recepção dos apátridas russos da China (1949 – 1964) - Santos, Bruna Soares dos (Universidade Federal de São Carlos, 2024)
The main objective of this study is to investigate the role of the Brazilian state in the international governance of refugees between 1949 and 1964. The period is characterised by the emergence of the international legal framework for the protection of refugees (1951 Convention relating to the Status of Refugees) and the United Nations High Commissioner for Refugees (UNHCR). The empirical case investigated was the process of Brazil's reception of stateless Russians expelled from China in 1949. The documents produced by the Brazilian Ministry of Foreign Affairs in the 1950s were analysed. They are stored in the collection of the Historical and Diplomatic Museum at the Itamaraty Palace (RJ). The exchanges of correspondence (letters and telegrams) between the Representative Office in Rio de Janeiro and the Consulate General of Brazil in Hong Kong between 1947 and 1959 were examined. Through these records, the project sought to understand the selection criteria and the reasons for accepting these refugees in Brazil. It sought to investigate how these actions constructed the figure of the desirable refugee, especially when it came to elements such as body, gender, religion, marital status, qualifications and professional occupation. As a result, it was found that the humanitarian motivation concealed the Brazilian government's economic and political interests in bringing professionally, morally and religiously qualified people to Brazil.
Brazil on the threshold of international refugee law: Itamaraty and the reception of stateless russians from China (1949 - 1964)
Keywords: Imigração; Refúgio; China; Brasil; Segunda Guerra Mundial; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS